TONIC IMMOBILITY TECHNIQUE AS INDICATORS OF STRESS ON CHICKEN IN THE MAINTENANCE OF INTENSIVE WITH INTERMITTENT LIGHTING - Sulistyoningsih, Mei (BIOMA, 2011)
Lighting is an important part of poultry production. Lighting is a powerful exogen-ous factor in controlling many physiological and behavioral processes. Lighting is the most critical factor of all the environmental factors for poultry. The research aims to (1) assess the influence of intermittent lighting in intensive maintenance chickens on chicken that has been commonly maintained by to let loose (removed), (2) examine how to overcome the possibility of stress that arise in chic-kens which are usually removed, then maintained in a way grounded. The study design used was completely randomized design (CRD) in time, with three treatments are: C1 = illumination 1L: 3D: C2 = lighting 2L: 2D; and C3 = lighting 12L: 0D. Each treatment was repeated four times. The parameters studied were body weight, technique tonic immobility, and mortality. Data were analyzed and interpret- ted by analysis of variance. The results are, the imposition of intermittent lighting on the maintenance of inten-sive chicken on a scale of households, providing a positive and beneficial influence on the production aspect of weight loss and mortality. Intermittent lighting will mi-nimize the risk of stress in chickens as seen on tonic immobility technical para-meters of this study. The best performance results seen in treatment C1 (1L: 3D), the treatment of intermittent one-hour light, and 3 hours of darkness each day, from 18:00 until 06:00 hours for 10 weeks, starting the second week of the study. The conclusion is intermittent lighting treatment in the intensive maintenance chic-kens on chicken that has been commonly maintained by to let loose positive effect that can increase body weight, reduce mortality and minimize the risk of stress.Keywords: Chicken, intermittent lighting, tonic immobility